1982
DOI: 10.1139/v82-354
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic non-equivalence of fluorine atoms of a trifluoromethyl group

Abstract: The three fluorine atoms of N,N-dialkyl amide and chloride derivatives of 2-methoxy-2-phenyl-3,3,3-trifluoropropanoic acid are magnetically nonequivalent below –60 °C and exhibit a clear ABC coupling pattern from which chemical shifts and geminal coupling constants are readily derived. The chemical shifts span a range of about 10 ppm and the geminal coupling constants average about 110 Hz. A five bond coupling of about 5 Hz is observed between the hydrogens of the methoxy group and one of the nonequivalent flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…(c) Comparison with Other Examples of Hindered CF 3 Rotation. Of the thousands of known compounds containing CF 3 groups, before this work only 27 of them were reported to exhibit slow-exchange-limit 19 F NMR spectra, and all but two of these required temperatures that ranged from −60 °C to −190 °C. ,, Representative compounds are listed in Table (see Supporting Information for a complete list of all compounds). The 113-Hz 2 J AB value exhibited by 1,9-C 60 F(CF 3 ) and C s -C 60 F 17 (CF 3 ) is in the middle of the 97−137-Hz range for the previously reported compounds, while the 105−126-Hz range of 2 J FF values for C 1 -C 60 F 17 (CF 3 ) spans a significant portion of the previous range.…”
Section: Resultsmentioning
confidence: 99%
“…(c) Comparison with Other Examples of Hindered CF 3 Rotation. Of the thousands of known compounds containing CF 3 groups, before this work only 27 of them were reported to exhibit slow-exchange-limit 19 F NMR spectra, and all but two of these required temperatures that ranged from −60 °C to −190 °C. ,, Representative compounds are listed in Table (see Supporting Information for a complete list of all compounds). The 113-Hz 2 J AB value exhibited by 1,9-C 60 F(CF 3 ) and C s -C 60 F 17 (CF 3 ) is in the middle of the 97−137-Hz range for the previously reported compounds, while the 105−126-Hz range of 2 J FF values for C 1 -C 60 F 17 (CF 3 ) spans a significant portion of the previous range.…”
Section: Resultsmentioning
confidence: 99%
“…This extended form was also observed as the major conformer in the MTPA esters, along with the other minor conformers [9]. Khan et al reported that θ 2 was relaxed to +50° using the MNDO method in the case of (R)-N,N′-dimethyl-3,3,3-trifluoro-2-methoxy-2-phenylpropanamide [75]. …”
Section: Conformation Of the Methoxy Group: C1-c2-o2-c4mentioning
confidence: 92%
“…This was suggestive of the staggered conformation of the trifluoromethyl group [9]; that is, the two oxygen atoms O1 and O2 were as far as possible from the fluorine atoms. F-NMR spectra at low temperatures [75]. They also reported that barriers to the hindered rotation on the C2-C3 bonds were in the range of 36-46 kJ/mol.…”
Section: Staggered Conformation Of Trifluoromethyl Group: C1-c2-c3-f3mentioning
confidence: 94%
“…1 -3 After initial studies on the applications of Mosher's method to secondary amines by Tavares and coworkers, 4,5 Hoye and Renner summarized the common characteristics of 1 H NMR spectra of Mosher's amides derived from cyclic secondary amines with a chiral center in the ring. 6,7 It has been proved that Hoye's protocol can be an efficient guideline for assigning the absolute configuration or enantiomeric excess of substituted cyclic secondary amines.…”
Section: Introductionmentioning
confidence: 99%